2012
DOI: 10.1100/2012/236427
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers of Dental Pulp Tissue during Orthodontic Tooth Movement: A Pilot Study

Abstract: Three specific orthodontic tooth movement genes, that is, FCRL1, HSPG2, and LAMB2 were detected at upper first premolar (with appliance) dental pulp tissue by using GeneFishing technique as compared to lower first premolar (without appliance). These three differentially expressed genes have the potential as molecular markers during orthodontic tooth movement by looking at molecular changes of pulp tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Recent study reported that knockdown of PRPF8 significantly impairs mitophagosome formation, thus, these findings demonstrate that PRPF8 is essential for mitophagy and suggest that dysregulation of spliceosome-mediated mitophagy may contribute to pathogenesis of disease such as cancer [22]. PRPF8 is a highly conserved pre-mRNA splicing factor and a component of spliceosomal small nuclear ribonucleoproteins (snRNPs), which is essential in RNA and mRNA splicing through transesterification and spliceosome processes [23]. It was reported that the events of splicing were related to tumor progression, the alternative splicing of different pre-mRNAs is altered during oncogenic progression with the concomitant development of cancer features, like an increase in vascularization, cell proliferation, and invasion [24].…”
Section: Discussionmentioning
confidence: 87%
“…Recent study reported that knockdown of PRPF8 significantly impairs mitophagosome formation, thus, these findings demonstrate that PRPF8 is essential for mitophagy and suggest that dysregulation of spliceosome-mediated mitophagy may contribute to pathogenesis of disease such as cancer [22]. PRPF8 is a highly conserved pre-mRNA splicing factor and a component of spliceosomal small nuclear ribonucleoproteins (snRNPs), which is essential in RNA and mRNA splicing through transesterification and spliceosome processes [23]. It was reported that the events of splicing were related to tumor progression, the alternative splicing of different pre-mRNAs is altered during oncogenic progression with the concomitant development of cancer features, like an increase in vascularization, cell proliferation, and invasion [24].…”
Section: Discussionmentioning
confidence: 87%
“…HSPG2 expression is activated in the dental pulp when orthodontic force is applied. The protein is important in repairing and remodeling ECM in tissue stroma and basement membrane [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent study reported that knockdown of PRPF8 signi cantly impairs mitophagosome formation, thus, these ndings demonstrate that PRPF8 is essential for mitophagy and suggest that dysregulation of spliceosome-mediated mitophagy may contribute to pathogenesis of disease such as cancer [22]. PRPF8 is a highly conserved pre-mRNA splicing factor and a component of spliceosomal small nuclear ribonucleoproteins (snRNPs), which is essential in RNA and mRNA splicing through transesteri cation and spliceosome processes [23].…”
Section: Discussionmentioning
confidence: 94%